Familial sarcoidosis terminating as neurosarcoidosis. Issue 528 (October 1969) - Salm, R.
Abstract : A case of sarcoidosis is recorded in a 27-year-old male, whose elder sister has also been suffering from sarcoidosis. The disease was characterized by involvement of the mucosa of the upper respiratory tract, gross transient peripheral lymphadenopathy and terminal neurosarcoidosis, death being due to an acute obstructive hydrocephalus.